2008
DOI: 10.1017/s0959270908000312
|View full text |Cite
|
Sign up to set email alerts
|

The generation and use of bird population indicators in Europe

Abstract: Global and regional targets to reduce the rate of biodiversity loss bring with them the need to measure the state of nature and how it is changing. A number of different biodiversity indicators have been developed in response and here we consider bird population indicators in Europe. Birds are often used as surrogates for other elements of biodiversity because they are so well known and well studied, and not for their unique intrinsic value as environmental indicators. Yet, in certain situations and at particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 23 publications
0
61
0
1
Order By: Relevance
“…Gage and Miller (1978) used human acoustic observations to document avian responses to spruce budworm over 22 yr ;Inger et al (2014) used a 30 yr dataset on 144 bird species to demonstrate the decline of common bird populations in Europe; and Gregory et al (2005) demonstrated the decline of farmland birds with data collected from 18 countries between 1980 and 2004. Given the availability of high-quality bird data and the fact that birds exhibit wide geographic and habitat distribution and play diverse roles in ecosystem functioning, bird population trends are often used as indicators of environmental change (Sekercioglu 2006, Gregory et al 2008, Sheehan et al 2010. For example, the Wild Bird Index (WBI) was developed to evaluate progress toward the international goal of reducing the global rate of biodiversity loss (Butchart et al 2010, Sheehan et al 2010).…”
Section: Principles Of Soundscape Ecology Related To Avian Ecology Ementioning
confidence: 99%
“…Gage and Miller (1978) used human acoustic observations to document avian responses to spruce budworm over 22 yr ;Inger et al (2014) used a 30 yr dataset on 144 bird species to demonstrate the decline of common bird populations in Europe; and Gregory et al (2005) demonstrated the decline of farmland birds with data collected from 18 countries between 1980 and 2004. Given the availability of high-quality bird data and the fact that birds exhibit wide geographic and habitat distribution and play diverse roles in ecosystem functioning, bird population trends are often used as indicators of environmental change (Sekercioglu 2006, Gregory et al 2008, Sheehan et al 2010. For example, the Wild Bird Index (WBI) was developed to evaluate progress toward the international goal of reducing the global rate of biodiversity loss (Butchart et al 2010, Sheehan et al 2010).…”
Section: Principles Of Soundscape Ecology Related To Avian Ecology Ementioning
confidence: 99%
“…Again, we used TRIM to estimate the missing country totals, in a way equivalent to imputing missing counts for particular sites. This procedure was trialed in van Strien et al (2001) and has been applied subsequently by Gregory et al (2005Gregory et al ( , 2007Gregory et al ( , 2008. We combined the all-sites totals in five regional groupings (see Table 1).…”
Section: Producing Supranational Indices and Trendsmentioning
confidence: 99%
“…Specifically, we examine trends in European bird abundance in different habitats with the strong expectation that grouped species trends will differ by habitat, by region and by migratory status of the species following our previous work (Gregory et al 2005(Gregory et al , 2007(Gregory et al , 2008. We focus our attention on widespread farmland birds, but to provide context, we also present trends for all the species monitored by the PECBMS and trends for common forest birds too.…”
mentioning
confidence: 99%
“…These include the international Living Planet Index (Loh et al 2005, Hails et al 2008; Fig. 1) and the UK's Wild Bird Indicators (BTO 2011, Gregory et al 2008, Gregory and van Strien 2010Fig. 2).…”
Section: Introductionmentioning
confidence: 99%